2016
DOI: 10.3390/ijms17111797
|View full text |Cite
|
Sign up to set email alerts
|

The Activating NKG2C Receptor Is Significantly Reduced in NK Cells after Allogeneic Stem Cell Transplantation in Patients with Severe Graft-versus-Host Disease

Abstract: Natural killer (NK) cells play a central role in the innate immune system. In allogeneic stem cell transplantation (alloSCT), alloreactive NK cells derived by the graft are discussed to mediate the elimination of leukemic cells and dendritic cells in the patient and thereby to reduce the risk for leukemic relapses and graft-versus-host reactions. The alloreactivity of NK cells is determined by various receptors including the activating CD94/NKG2C and the inhibitory CD94/NKG2A receptors, which both recognize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
(38 reference statements)
1
32
1
Order By: Relevance
“…As mentioned above, evidence for the recovery of NK cell receptor subsets after stem cell transplantation is scarce. In a prospective study Kordelas et al [19] monitored the frequencies of inhibitory receptor CD94/NKG2A expression in NK cells after the allo-HSCT course for 1 year and related the results to the occurrence of severe aGVHD or chronic GVHD in a cohort of 26 patients undergoing allo-HSCT. This study showed that the NKG2A receptor continuously decreased in the first year after allo-HSCT and that the NKG2A + subset was reduced in chronic GVHD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, evidence for the recovery of NK cell receptor subsets after stem cell transplantation is scarce. In a prospective study Kordelas et al [19] monitored the frequencies of inhibitory receptor CD94/NKG2A expression in NK cells after the allo-HSCT course for 1 year and related the results to the occurrence of severe aGVHD or chronic GVHD in a cohort of 26 patients undergoing allo-HSCT. This study showed that the NKG2A receptor continuously decreased in the first year after allo-HSCT and that the NKG2A + subset was reduced in chronic GVHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NKG2A + NK cells have been proposed to play a crucial role during the early stage of GVHD after transplantation. Previous studies have shown that the number of NKG2A + cells is decreased in patients with chronic GHVD after HSCT [19]. However, the relationship between NKG2A + NK cells and aGVHD has not been characterized.…”
mentioning
confidence: 95%
“…In contrast, these results were not found in patients with high-risk disease [14]. Moreover, expression of the activating NKG2C receptor (another member of the NKG2 family) is significantly lower in NK cells after HSCT in patients with severe GVHD [15]. We can therefore hypothesize that donor NK cells, with a low level of cytotoxic activity against host-type antigen-presenting cells, might promote GVHD via CD8+ cells [16].…”
mentioning
confidence: 89%
“…The disclosure of potential alloreactive uCD56 dim NK cells expanded early after allo‐ and haplo‐HSCT has arisen new important questions. Indeed, the constitutive expression of CD94/NKG2A on almost all NK cells early after HSCT represents a novel targetable immune‐checkpoint to boost NK cell alloreactivity early after transplant in order to prevent acute and chronic GvHD, the onset of opportunistic infection and to ensure an optimal engraftment …”
Section: Nk Cell Immune‐reconstitution and Nkg2a In Hsctmentioning
confidence: 99%